Selected integrated farming system models for enhanced income - Srivastava, A. P. (Indian Farming, 2019)
Under National Agricultural Innovation Project (NAIP), supported by the World Bank and implemented by Indian Council of Agricultural Research (2006-14), an effort was made to enhance income of the rural people living in selected disadvantaged regions through technologyled innovation systems. Very often emphasis on one component in rural areas, particularly among those people whose livelihood is threatened can not lead to overall livelihood improvement of a household. Accordingly, interventions in IFS mode (crop-livestock- aquaculture) were planned and demonstrated, keeping in view the overall need of the area, available technological options, market accessibility both for input and produce etc. Some of the IFS models demonstrated with success are disucussed here.